The traditional ethnic herb Tadehagi triquetrum from China: a review of its phytochemistry and pharmacological activities. (31st December 2022) - Tang, Hong-Xia; Sheng, Wen-Bing; Liu, Xin-Yi; Cui, Pei-Wu; Gong, Li-Min; Xie, Qing-Ling; Wang, Wen-Mao; Li, Bin; Wang, Wei; Zhou, Xu-Dong
Abstract: Context: Tadehagi triquetrum (Linn.) Ohashi (Fabaceae) ( TT ), is a traditional herbal medicine used especially in China's ethnic-minority communities, such as the Zhuang, Dai, Li and Wa aeras. As an ethnic medicine, it has long been used to treat various diseases. Objective: This review summarised the phytochemical and pharmacological progress on TT from 1979 to October, 2021 by highlighting its chemical classification, structural features, pharmacological applications and folk applications to provide inspirations and suggestions for accelerating further research of this traditional phytomedicine. Methods: The information on TT in this article has been obtained using these multiple scientific databases including Scifinder, Web of Science, ScienceDirect, Wiley, ACS publications, Springer, PubMed, China Knowledge Resource Integrated Database from the China National Knowledge Infrastructure (CNKI), Google Scholar and Baidu Scholar. Some information was also collected from classic literature on traditional Chinese medicines. Results: More than 70 compounds have been isolated and reported from TT to date by the comprehensive analysis of the current literature. A large number of traditional uses and pharmacological studies have exhibited diversified bioactivities of various TT extracts and its metabolites, including anti-inflammatory, antimicrobial, anti-hepatitis B virus, hepatoprotective, insecticidal, etc. Conclusions: As a famous traditional medicine with a long history, TT has various medicinal uses and some of them have been supported by modern pharmacological researches. Further detailed studies on the action mechanisms, pharmacodynamics and structure-function relationships of single compounds or active constituents from TT are also required.